The Relationship between Service Quality and Outpatient Satisfaction at the Langga Payung Health Center, South Labuhanbatu Regency in 2022 - Irwan Agustian (Institute of Computer Science (IOCS), 2022)
Community satisfaction with health services is not only related to recovery from illness. Community satisfaction is related to the quality of service at the Puskesmas. Service quality is divided into five dimensions, namely physical evidence, reliability, responsiveness, assurance and empathy. This study aims to determine the relationship between service quality and outpatient satisfaction at the Langga Payung Health Center in South Labuhanbatu Regency in 2022. This research is a quantitative study with a cross-sectional approach. This research was conducted from 30 May 2022 to 11 June 2022. The population in this study was 68 people per month. The sampling technique used accidental sampling technique totaling 54 people. Data analysis techniques through coding (coding data), editing (data checking), tabulation (data grouping), Entry (data entry) and Processing (data processing). The results of the study found that there was no relationship between physical evidence (tangible) and outpatient satisfaction at the Langga Payung Health Center in Labuhanbatu Selatan Regency in 2022 with a p value = 0.103 < α = 0.05, there was a reliability relationship with outpatient satisfaction at Langga Payung Health Center in South Labuhanbatu Regency in 2022 with a p value = 0.017 <α=0.05, there is a relationship between responsiveness and outpatient satisfaction at the Langga Payung Health Center in South Labuhanbatu Regency in 2022 with a p value = 0.005 <α = 0.05, there is a relationship between assurance and patient satisfaction at the Langga Payung Health Center in South Labuhanbatu Regency in 2022 with a p value = 0.001 < α = 0, 05 and there is a relationship between empathy and outpatient satisfaction at the Langga Payung Health Center in South Labuhanbatu Regency in 2022 with a p value = 0.004 < α = 0.05. Suggestions in this study, especially for health workers should continue to strive to improve the quality of service so as to increase patient satisfaction for treatment so that the level of public health is getting better